Application of Home-Based Wearable Technologies in Physical Rehabilitation for Stroke: A Scoping Review - Sharon Fong Mei Toh; Kenneth N. K. Fong; Pablo Cruz Gonzalez; Yuk Ming Tang (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Using wearable technologies in the home setting is an emerging option for self-directed rehabilitation. A comprehensive review of its application as a treatment in home-based stroke rehabilitation is lacking. This review aimed to 1) map the interventions that have used wearable technologies in home-based physical rehabilitation for stroke, and 2) provide a synthesis of the effectiveness of wearable technologies as a treatment choice. Electronic databases of the Cochrane Library, MEDLINE, CINAHL, and Web of Science were systematically searched for work published from their inception to February 2022. This scoping review adopted Arksey and O’Malley’s framework in the study procedure. Two independent reviewers screened and selected the studies. Twenty-seven were selected in this review. These studies were summarized descriptively, and the level of evidence was assessed. This review identified that most research focused on improving the hemiparetic upper limb (UL) function and a lack of studies applying wearable technologies in home-based lower limb (LL) rehabilitation. Virtual reality (VR), stimulation-based training, robotic therapy, and activity trackers are the interventions identified that apply wearable technologies. Among the UL interventions, “strong” evidence was found to support stimulation-based training, “moderate” evidence for activity trackers, “limited” evidence for VR, and “inconsistent evidence” for robotic training. Due to the lack of studies, understanding the effects of LL wearable technologies remains “very limited.” With newer technologies like soft wearable robotics, research in this area will grow exponentially. Future research can focus on identifying components of LL rehabilitation that can be effectively addressed using wearable technologies.